Student’s Metacognitive Awareness in Mobile based Reading Test - Nur Kamilatur Rosyidah; M. Syaichul Muhyidin; Irwan Sulistyanto (Universitas Uluwiyah Mojokerto, Indonesia., 2026)
The growing use of mobile-based assessment platforms has changed the ways students interact with reading tasks and created new cognitive challenges during reading. The purpose of this study was to find out the implementation of metacognitive awareness of English Education students in the mobile-based reading test, the challenges faced by the students and the strategies used to overcome the challenges. This study used a qualitative approach with a phenomenological design. The participants were seven students of the second semester of the English Education Study Program at the Islamic University of Kadiri, Indonesia. Data were collected by means of semi-structured interviews and analyzed through transcription, coding, thematic analysis and phenomenological interpretation. The findings resulted in three major themes. First, students experienced metacognitive awareness through planning, monitoring and self-regulation strategies including goal setting, text previewing, activating prior knowledge and evaluating comprehension while reading. Second, participants encountered several metacognitive challenges such as concentration, understanding complex texts, unfamiliar vocabulary, and technical limitations (scrolling and limited screen displays). Thirdly, students used a variety of adaptive strategies to tackle the challenges, including rereading, minimizing distractions, utilizing translation apps like Google Translate, and highlighting key information on the screen. The findings suggest that metacognitive awareness plays a significant role in helping students regulate their comprehension and adapt to the cognitive demands of mobile-based reading environments. This study adds to the expanding literature on metacognition and digital reading by offering an understanding of students lived experiences in technology-mediated assessment contexts.